The Effectiveness Of Popular Songs In Teaching Listening Comprehension To The Eight Grade Students’s At SMP Negeri 1 Palu - Fidyah, Fidyah; Arid, Muhammad; Lebagi, Desrin; Dewi, Anjar Kusuma (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of popular songs in teaching listening skills to eighth-grade students at SMP Negeri 1 Palu. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of two classes: an experimental group taught using popular songs and a control group taught using conventional methods. The research instrument was a listening comprehension test administered before (pretest) and after (posttest) the treatment. Data analysis used the Mann-Whitney U test to compare posttest scores between groups and the Wilcoxon Signed-Rank test to compare pretest and posttest scores within each group. The results revealed a significant difference between the experimental and control groups (p 0.05), with the experimental group achieving a higher posttest mean score (94.63) than the control group (85.66). The improvement in the experimental group was also greater than in the control group. Therefore, it can be concluded that the use of popular songs is more effective than conventional methods in enhancing students’ listening skills.